Law and ethics in nursing and healthcare - Avery, Graham (SAGE Publishing, 2017)
A concise, highly accessible introduction to the key legal requirements needed to practice professionally within nursing and healthcare - a core element of the undergraduate nursing and healthcare curriculum. Each chapter supports theoretical learning with learning objectives, legislative case examples and practical scenarios.